Does muscle imbalance affect fatigue after soccer specific intermittent protocol? - de Abreu Camarda, S. R.; Denadai, B. S. (Journal of Science and Medicine in Sport, 2012)
This study investigated the muscular strength imbalance dependence of the effect of fatigue induced by an exhaustive laboratory-based soccer-specific exercise on different hamstrings:quadriceps (H:Q) ratios of soccer players.